Rheological Performance of Asphalt Mastics Incorporating Shale and Pumice as Alternative Mineral Fillers - Suwaphit Chamwon; Multazam Hutabarat; Preeda Chaturabong (Salehan Institute of Higher Education, 2026)
This study investigates the hypothesis that mineral fillers with distinct surface characteristics, mineralogical compositions, and morphologies exhibit different reinforcement mechanisms in asphalt mastics. Shale and pumice were evaluated as alternative mineral fillers and compared with conventional granite and limestone at 20% and 30% filler-to-asphalt (F/A) ratios by volume. Filler characterization included X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), specific surface area (SSA), and hydrophilicity coefficient (HC) measurements. Rheological characterization was performed using dynamic shear rheometer, including temperature sweep, frequency sweep master curves, multiple stress creep recovery (MSCR), linear amplitude sweep (LAS), and Glover–Rowe (G–R) analyses. Pumice, dominated by amorphous volcanic glass with the highest SSA (59.18 m²/g), exhibited rutting-dominant modification with the highest complex modulus enhancement (7.3–9.4 times at 30% F/A) and lowest non-recoverable creep compliance. Shale, composed primarily of quartz and kaolinite with layered morphology and moderate SSA (43.00 m²/g), demonstrated balanced rheological response and achieved the longest fatigue life (Nf,5% = 45,200 cycles at 20% F/A). These findings demonstrate that filler-specific reinforcement mechanisms are governed by mineralogical composition and morphology, supporting performance-based filler selection tailored to climatic and loading conditions.